ARGAMASSAS AUTONIVELANTES PARA PISOS: CONTRIBUIÇÃO DOS FINOS RESIDUAIS - Carvalho, Henrique Duarte Sales; Cheriaf, Malik; Rocha, Janaíde Cavalcante (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Self-levelling mortar are a fluid product that has as a low viscosity and high fluidity. This mortars requires no vibration and levelling, having very low thickness (30 mm). The purpose of this study was to evaluate fresh properties of self-levelling SLU using three by-products: bottom-ashes, fine elements of quarry limestone and fine elements from recycled-concretewaste. Portland Cement OPC was partially replaced by 0,10%, 15% e 20% of fines. The water/binder was fixed at 0.50 and mix proportion 1:2 cement and sand (by weight) was used. Fresh properties were examined: flow, plastic shrinkage and curling. The curling phenomenon is high (more than 1,70 mm to mortar based on fine from recycled concrete waste). Higher early curling was obtained to mortar with quarry limestone. A good performance could be assured with ternary mixes with bottom ashes (curling less than 1mm).